The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5194/tc-7-1333-2013
|View full text |Cite
|
Sign up to set email alerts
|

<i>Brief Communication</i> "The 2013 Erebus Glacier Tongue calving event"

Abstract: Abstract. The Erebus Glacier Tongue, a small floating glacier in southern McMurdo Sound, is one of the beststudied ice tongues in Antarctica. Despite this, its calving on the 27 February 2013 (UTC) was around 10 yr earlier than previously predicted. The calving was likely a result of ocean currents and the absence of fast ice. The subsequent trajectory of the newly created iceberg supports previous descriptions of the surface ocean circulation in southern McMurdo Sound.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…This is superimposed upon a steadier westward flow strong enough to prevent current reversal (Fig. 4b) either through flow rectification or regional circulation (Stevens et al, 2011(Stevens et al, , 2014. This was confirmed over a 10-day period beginning on DOY 300, where currents measured in the upper 60 m of the water column at the Mast B site ranged from 0.03 to 0.28 m s −1 westward (Stevens et al, 2014).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…This is superimposed upon a steadier westward flow strong enough to prevent current reversal (Fig. 4b) either through flow rectification or regional circulation (Stevens et al, 2011(Stevens et al, , 2014. This was confirmed over a 10-day period beginning on DOY 300, where currents measured in the upper 60 m of the water column at the Mast B site ranged from 0.03 to 0.28 m s −1 westward (Stevens et al, 2014).…”
Section: Resultsmentioning
confidence: 59%
“…In October and November 2010, the New Zealand National Institute of Water and Atmospheric Research (NIWA) established a temporary station, Erebus Field Camp (EFC), on fast (immobile) sea ice near Erebus Glacier tongue (EGT) in Mc-Murdo Sound, Antarctica. The general layout of EFC and its location relative to nearby geographic features is described by Stevens et al (2014Stevens et al ( , 2011 and shown in Fig. 2.…”
Section: Field Camp and Instrumentationmentioning
confidence: 99%
“…At the time of the sampling, the most recent calving of the EGT had been in March 1990 when a 3.5 km section broke away [ Robinson and Haskell , ]. Subsequent to the observations described here, a 4 km section calved off in February 2013 [ Stevens et al ., ]. Similar events were known to have occurred in 1911 and at some point during the 1940s [ Holdsworth , ].…”
Section: Methodsmentioning
confidence: 64%
“…Another 1 km farther toward Ross Island, a large crack on the south side of the tongue was sufficiently open so as to be penetrated by skidoo traveling on the sea ice. This halved the structural width of the EGT and subsequently was the location for the February 2013 calving [ Stevens et al ., ].…”
Section: Resultsmentioning
confidence: 99%
“…Expeditions to variously evocatively named remote icy locations [e.g. Stevens et al, 2013], the Drygalski Ice Tongue, the Erebus Glacier Tongue, the Ross Ice Shelf and Haskell Strait are all connected with different parts of the role ice in Antarctica plays in our global system. The science has its similarities to the art in that achievable elements are joined to form a larger whole.…”
Section: Methods: the Classroom Processmentioning
confidence: 99%